The York Explosion- or Battiering and Bumbarding the Tenth!! - (:unkn) unknown (My University, 1824)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Batt's report; Great Britain. ? Army. ? Royal Hussars, 10th; York (England)